2015
DOI: 10.1016/j.chembiol.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The Tetracycline Destructases: A Novel Family of Tetracycline-Inactivating Enzymes

Abstract: Summary Enzymes capable of inactivating tetracycline are paradoxically rare compared with enzymes that inactivate other natural product antibiotics. We describe a family of flavoenzymes, previously unrecognizable as resistance genes, which are capable of degrading tetracycline antibiotics. From soil functional metagenomic selections, we discovered nine genes that confer high-level tetracycline resistance by enzymatic inactivation. We also demonstrate that a tenth enzyme, an uncharacterized homolog in the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
162
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 61 publications
4
162
0
2
Order By: Relevance
“…3), and found to convert chlortetracycline ( m/z 479) to an oxidation product with an m/z of 467. This is in contrast to the m/z 461 monooxygenation product observed for tetracycline 28 , consistent with an alternate binding mode for chlortetracycline. To further characterize this product, reactions were subjected to high resolution mass spectrometry (Fig.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…3), and found to convert chlortetracycline ( m/z 479) to an oxidation product with an m/z of 467. This is in contrast to the m/z 461 monooxygenation product observed for tetracycline 28 , consistent with an alternate binding mode for chlortetracycline. To further characterize this product, reactions were subjected to high resolution mass spectrometry (Fig.…”
Section: Resultssupporting
confidence: 66%
“…We reasoned that a similar strategy might be useful to counteract tetracycline resistance by inactivation, and therefore sought to identify small molecule inhibitors of these enzymes. Previously, we observed that anhydrotetracycline, a key biosynthetic precursor 41 and degradation product 42 of tetracycline with poor antibiotic activity was not degraded by Tet(47-56) 28 . None the less, it is known to be an effector of tetracycline producers and tetracycline-resistant bacteria by inducing expression of energetically expensive tetracycline efflux pumps, permitting tetracycline producers to survive and selecting against tetracycline resistance 43 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations